Meningkatan Kemampuan Hafalan Struktur Gerak Tari dengan Metode Drill And Practice - Intan yuliyanti; Agus Budiman (Mahesa Research Center, 2023)
Dance learning needs to have competence in memorizing the structure of dance movements. One way to improve the ability to memorize dance movement structure material can be developed with the drill and practice method. However, currently most students who take part in extracurricular dance lack the ability to memorize dance movements so that it can cause the learning objectives not to be achieved. The purpose of this study was to find solutions to learning problems in mastering the memorization of dance movements in extracurricular dance activities at one of the Vocational High Schools in Cimahi City. This research was conducted using the action research method. Data collection techniques used observation, interviews and action tests on students who participated in extracurricular dance activities as many as 26 students. In the initial stage, a questionnaire or questionnaire was also given in the form of a google form to find out the level of students' memorization ability in mastering the dance motion material that had been given by the teacherThe results of this study show the ability to increase memorization of dance movements that can be seen when students are able to demonstrate dance movements without making mistakes. The results of the study can be used as recommendations to dance teachers who will improve student learning outcomes in dance extracurricular activities at school, especially in improving students' memorization skills.